New replacement names for Oriental Scydmaeninae (Coleoptera, Staphylinidae) - Jałoszyński, Paweł (Zootaxa, 2011)
During the preparation of a catalogue of Oriental Scydmaeninae several cases of homonymy were discovered, including a junior homonym preoccupied by two names established in a single previous article, all by the same author. Original descriptions clearly present different species, and therefore cases of duplicate descriptions can be excluded. Herein, replacement names for the homonyms are proposed.